Associations between levels of physical literacy and adherence to the 24-h movement guidelines among university students: A cross-sectional study - Y. Liu; S.X. Liu; R.K.W. Sum; M.J. Duncan; Y.D. Gu; M.H. Li (Elsevier, 2024)
Objectives: Emerging evidence indicates that the composition of movement behaviours within a 24-h period is associated with multiple health benefits across the lifespan. A concept that emphasises an individual's active lifestyle is physical literacy (PL), yet empirical research exploring the potential associations between PL and 24-h movement guidelines remains scarce. This study aimed to evaluate the associations between levels of PL and adherence to the guidelines among Chinese university students. Study design: A cross-sectional study. Methods: Seven hundred and ninety-eight university students (390 male, 19.2 ± 1.2 years) completed all the measurements. Levels of PL and participants' adherence to guidelines including physical activity, sedentary behaviour and sleep were self-reported through Perceived Physical Literacy Instrument, International Physical Activity Questionnaire and Pittsburgh Sleep Quality Index, respectively. Two-way ANOVA was conducted to determine the associations between the number of guidelines met (0, 1, 2, or 3) and levels of PL. Results: The results demonstrate that 36.5% (n = 291) of the participants met all the three guidelines, while 4.1% (n = 33) met none. Further analysis indicated that meeting physical activity or sedentary behaviour guidelines was associated with significantly higher total PL scores, and scores in the sub-domains of Confidence and Physical Competence and Motivation. Conclusions: The findings provide evidence that young adults who obtained higher PL scores may meet more guidelines during a 24-h period. Future studies should incorporate accelerometer-based physical activity measurements and investigate the causal relationship between PL and adherence to the movement guidelines.